Laparoscopic ultrasound and cholecystectomy: a small but vital parade - Deziel, Daniel J. (Laparoscopic Surgery, 2018)
The article by Dili and Bertrand: “Laparoscopic ultrasonography as an alternative to intraoperative cholangiography during laparoscopic cholecystectomy”, published in the World Journal of Gastroenterology, examines the attributes and limitations of laparoscopic ultrasonography as a method for imaging the bile ducts during laparoscopic cholecystectomy (1).